Review: Pemanfaatan Nanosains dan Nanoteknologi untuk Meningkatkan Efektivitas Obat - Indrawati, Teti (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2023)
Science and nanotechnology in the pharmaceutical field, among others, are used to increase drug effectiveness and optimal safety. The research was conducted using the review method with the aim of this study to obtain information about the utilization of nanoscience and nanotechnology which can be used as reference material for development in the pharmaceutical field. Nano-drug delivery system technology is carried out by developing materials used both from natural origin, synthetic, and semi-synthetic as well as developing drug delivery systems. Nano-drug delivery system technology or known as smart drugs promises a very bright future through various modifications of drug dosage forms developed from conventional dosage forms to dosage forms with drug delivery systems with controlled drug release. Nano-drugs with nano-delivery systems can be made using carriers in the form of natural polymers, or synthetic ones that can be biodegradable or non-biodegradable. Efficient therapy using nanotechnology is carried out in order to increase the safety level of the drug, as well as the ability of the drug to reach its target with minimal side effects. There are three ways to do this: increasing the solubility and bioavailability of drugs, creating new dosage forms, and using better routes of administration. Nanotechnology has great potential in contributing to the national economy and the nation's competitiveness, although much needs to be done to transform scientific and technological excellence into the economic field.